Stigmatizing Attitudes Toward COVID-19 Among Patients, Their Relatives and Healthy Residents in Zhangjiajie - Chen, Xinxin; Liao, Zhenjiang; Huang, Shucai; Huang, Qiuping; Lin, Shuhong; Li, Yifan; Shao, Tianli; Tang, Ying; Hao, Jingyue; Qi, Jing; Cai, Yi; Wang, Mingming; et al. (Frontiers in Public Health, 2022)
Introduction In July 2021, Zhangjiajie City became the new epicenter of the COVID-19 outbreak. Aside from the physical manifestations of COVID-19, patients are also victims of severe social stigmatization. Stigma affects not only COVID-19 patients or survivors, but also individuals associated with them. This study aims to describe and assess the COVID-19-related stigma between patients, their relatives, and healthy local residents. Methods The study included 43 COVID-19 patients, 68 relatives, and 75 healthy residents from Zhangjiajie. Demographic data was collected, including gender, age, marital status, and educational level. Stigma attitudes toward COVID-19 were measured using the Stigma Scale and Social Distance Scale. Frequencies and percentages were described for each item of the scales, and differences among the three groups were examined using the chi-square test. Results With regards to personal and perceived stigma, most participants agreed that patients with COVID-19 “could snap out of the problem” and that “they were dangerous.” For social distance, over 30% of participants from the three groups agreed with the item “unwillingness to marry into the family of someone with COVID-19.” In all groups, there were significant statistical differences in the belief that “the problem is not a real medical illness” and the desire to “spend the evening socializing.” Conclusion Although the outbreak was well-contained in Zhangjiajie, stigmatizing attitudes toward COVID-19 and desire for social distance to such patients were common among patients, their relatives and healthy local residents. Our study's results suggest that public education, anti-stigma interventions, and policies are necessary for people living in Zhangjiajie in order to effectively curtail the spread of COVID-19 and provide a useful strategy for a tourist city like Zhangjiajie to recover sooner from economic decline.